Physico-mathematical model for determining the direction in space to point sources of gamma radiation using spherical absorber - Grigoryev, A.N.; Bilyk, Z.V.; Pettersson, I.; Litvinov, Yu.V.; Polyansky, N.E.; Sakun, A.V.; Marushchenko, V.V.; Cherniavskyi, I.Yu.; Voronkin, E.F.; Sosnutska, O.O.; Petrukhin, S.Yu.; Indykov, S.N.; et al. (Functional Materials, 2018)
Physico-mathematical model for determining the direction in space to point sources of gamma radiation using a spherical absorber was developed. CdTe detectors of appropriate sizes are placed in the regular pyramid tops under absorber. The physico-mathematical model allowed, taking into account the exponential attenuation of gamma radiation by the absorber, to find the distance from the location of any CdTe sensor to the surface of sphere in any direction in space. Calculated information and signal received from the detectors, correlate to each other. The ratios found depend on the angle to the source of gamma radiation and represent the ratio of transmittance coefficients for four sensors. A methodology for locating the developed device in space, which allowed to obtain dependence of the calculated ratios from the angle in space for θ = 90° and φ from 0° to 360° in increments of 15° was proposed. Each direction in space corresponds to a set of six respective ratios.